Local gingival crevicular fluid, synovial fluid, and circulating levels of prolactin hormone in patients with moderately active rheumatoid arthritis and stage III and IV periodontitis before and after non-surgical periodontal treatment—a controlled trial - El-Wakeel, Naglaa Mohamed; Shalaby, Zienab Farid; Abdulmaguid, Rania Farouk; Elhamed, Sally Said Abd; Shaker, Olfat (Clinical oral investigations, 2023)
Objectives We aimed to investigate prolactin (PRL) levels in gingival crevicular fluid (GCF), synovial fluid, and serum in patients suffering from moderately active rheumatoid arthritis (RA) with and without periodontitis (P). Further, to evaluate the effect of non-surgical periodontal treatment on these levels compared to controls. Materials and methods Eighty subjects were divided into 4 groups: group 1: 20 patients with RA + P, group 2: 20 periodontitis patients (systemically healthy), group 3: RA patients (periodontally healthy), and group 4: healthy controls. Patients with periodontitis received scaling and root planning (SRP). PRL was measured using enzyme‐linked immunosorbent assay. Results At baseline, in GCF of RA + P group showed the highest mean PRL levels, followed by P group whereas groups 3 and 4 showed a statistically less values than the first 2 groups. Serum values showed non-significant difference between the first three groups, although higher than healthy controls. SRP reduced GCF and serum levels of PRL in both P groups as well as synovial fluid PRL in group 1. SRP caused no change in DAS scores while reduced ESR values were observed in group 1 after treatment. Conclusions Local GCF and synovial levels of PRL seem to be linked to the disease process of both periodontitis and rheumatoid arthritis than serum levels. SRP reduced these local levels. Clinical relevance In patients with RA and CP, local PRL seems to play a role in the association between the two conditions; further, periodontal treatment is essential to improve periodontal condition in RA patients. Trial registration Clinicaltrials.gov. Identifier: NCT04279691.